External apical root resorption of maxillary incisors after class I dentoskeletal malocclusion orthodontic treatment in extraction and non-extraction cases - Ulfah, Khairiyah; Evangelina, Ida Ayu; Mardiati, Endah; Elih, Elih (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2023)
ABSTRACTIntroduction: External apical root resorption (EARR) is one of the undesirable iatrogenic effects of orthodontic treatment. EARR is a non-infectious and asymptomatic damage that cause apical shortening of the root structure due to permanent loss of cementum and / or dentin. The etiology is multifactorial, which is a combination of individual biological variability and mechanical factors of treatment such as extraction. The aim of this study was to evaluate EARR of maxillary incisors after class I dentoskeletal malocclusion orthodontic treatment in extraction and non-extraction cases. Methods: This research was using descriptive comparative analytic method. Fifty two panoramic radiograph of patients who have done orthodontic treatment were used in this study. The sample were divided into two groups, twenty for extraction cases and thirty two for non-extraction cases. EARR was measured from the difference in the root-crown ratio of the maxillary incisors before and after orthodontic treatment using ImageJ software. Data analysis was tested using t-test. Results: The change in the root-crown ratio of the maxillary incisors after orthodontic treatment in both non-extraction and extraction groups showed a significant difference (p-value <0.05). The difference in the root-crown ratio of maxillary incisors after orthodontic treatment in the non-extraction group compared to the extraction group showed no significant difference (p-value> 0.05). Conclusion: There was differences between EARR of maxillary incisors in both extraction and non-extraction cases. There was no differences in EARR of maxillary incisors after class I dentoskeletal malocclusion orthodontic treatment between extraction and non-extraction cases.KEY WORDS: Root, resorption, maxillary, incisors, malocclusion, angle class IResorpsi akar apikal eksternal gigi insisif rahang atas sesudah perawatan ortodonti pada kasus ekstraksi dan non ekstraksi maloklusi dentoskeletal kelas IABSTRAKPendahuluan: Resorpsi akar apikal eksternal merupakan salah satu efek iatrogenik yang tidak diinginkan. Resorpsi ini merupakan kerusakan non infeksius dan asimtomatik dimana terjadi pemendekan apikal akar gigi karena kehilangan permanen sementum dan atau dentin. Etiologi kondisi ini bersifat multifaktorial, merupakan kombinasi dari variabilitas biologi individu dan faktor mekanis perawatan, salah satunya adalah tindakan ekstraksi. Tujuan penelitian menganalisis resorpsi akar apikal eksternal pada gigi insisif rahang atas sesudah perawatan ortodonti kasus ekstraksi dan non ekstraksi maloklusi dentoskeletal kelas I. Metode: Jenis penelitian deskriptif analitik komparatif. Sampel penelitian adalah radiografi panoramik pasien sebelum dan sesudah perawatan ortodonti sebanyak 52 sampel, dibagi dalam kelompok kasus ekstraksi 20 sampel dan non ekstraksi 32 sampel. Resorpsi akar apikal eksternal diukur dari selisih rasio panjang akar mahkota gigi insisif rahang atas sebelum dan sesudah perawatan ortodonti menggunakan software ImageJ. Analisis data diuji dengan t-test. Hasil: Perubahan rasio panjang akar mahkota gigi insisif rahang atas sesudah perawatan ortodonti pada kelompok ekstraksi maupun non ekstraksi menunjukkan perbedaan yang bermakna (p-value < 0,05). Perbedaan selisih rasio panjang akar mahkota gigi insisif rahang atas antara kelompok ekstraksi dan non ekstraksi, sebelum dan sesudah perawatan ortodonti menunjukkan hasil yang tidak bermakna (p-value > 0,05). Simpulan: Terdapat perbedaan resorpsi akar apikal eksternal pada gigi insisif rahang atas baik pada kasus non ekstraksi maupun ekstraksi. Tidak terdapat perbedaan resorpsi akar apikal eksternal gigi insisif rahang atas sesudah perawatan ortodonti di antara kasus ekstraksi dan non ekstraksi maloklusi dentoskeletal kelas I.KATA KUNCIResorps,i akar, insisif, rahang atas, maloklusi, Angle kelas I